Trigonometria no triângulo retângulo: uma proposta de sequência didática no Ensino Básico - LUCENA, Laecio Amaury da Silva (2020)
This research arose from the need to make the study of trigonometry concepts more attractive to high school students from public schools in the State of Maranhão. The problem situation that drives this research is the difficulty of students in learning trigonometry content and the difficulty of teaching that promotes the learning of male and female students from elementary to high school. Two didactic sequences were applied. One with the students of the ninth year of the Integrated Unit Antônio Fernandes de Sousa, a municipal school, located in the city of Gonçalves Dias, Maranhão. The other sequence was applied to the students of the first year of high school at Sulamita Lúcio do Nascimento, the only high school in the city of Gonçalves Dias. This work presents, in addition to the analysis of practices carried out, practical activity suggestions for working on the topic of Trigonometry in the Right Triangle, thus contributing to the development of the skills required in the students' daily lives. The didactic sequences applied in public schools allowed the teacher to better evaluate the execution of the contents. When observing the answers, he noticed the learning as well as the difficulties presented by the students in the study of Trigonometry. The sequences proved to be efficient from the perspective of teaching and learning.